FUNDAMENTALS OF DEVELOPING STUDENTS' PROFESSIONAL COMPETENCIES BASED ON AN INTEGRATIVE APPROACH - Ismoilov Elmurod Olloberdi o‘g‘li (American Journals, 2024)
This article presents the scientific basis for the development of students' professional competencies based on an integrative approach. The concept of professional competence is explained in detail using the definitions of this concept by Uzbek and foreign scholars. The analysis fully justifies the need to use the integration of mathematics, computer science and physics in the development of students' professional competencies.
Keywords: Competence, professional competence, integration, integration of disciplines, integrative approach, fundamental knowledge, curriculum, interactive method, professional adaptation, professional formation.